Order Preferencing and Market Quality on U.S. Equity Exchanges - Peterson, Mark A.; Sirri, Erik R. (Review of Financial Studies, 2003)
We present a detailed view of market quality in the presence of preferencing arrangements. A unique dataset provides the opportunity to measure trading costs of marketable orders and fill rates and ex post costs of limit orders across trading venues. For market orders, we find the primary exchange provides the lowest execution costs. However, the preferencing exchanges are no worse than, and in most cases better than, the nonpreferencing regional exchanges. For limit orders, the regionals execute limit orders more frequently than the primary market and with an ex post execution cost that is not very different from the primary market.